Analysis of Horse Riding Extracurricular Activities in Forming the Character of Students at Zam-zam Integrated Islamic School (ZIIS) in Banyumas Regency - Muhammad Ilham Ramadhani; Agus Raharjo; Sulaiman (Journal of Physical Education Health and Sport, 2024)
This research aims to determine the influence of extracurricular horse riding on the formation of brave, confident and responsible characters in students at the ZIIS modern Islamic boarding school and examine the psychological relationship that exists between students (horse riders) and horses. The research method uses mixed methods research by collecting, analyzing, and combining quantitative and qualitative research methods in a series of research. The samples taken for research were 25 male students and 25 female students. Each student was given a questionnaire containing questions regarding character formation after participating in equestrian extracurriculars. The results of observation data, interviews and questionnaires confirmed that an index in the range of 80% - 100%. The conclusion is the strong agreement among  respondents in the questionnaire that equestrian extracurriculars can form brave, confident, responsible characters and can form a psychological relationship between horse riders and horses.